Влияние изменения геометрических параметров на размеры ПВД и эффективность его работы - Михайлова, Ирина Александровна; Бабенко, А. С. (НТУ "ХПИ", 2011)
The evaluation of effect of change of geometrical characteristics in PV-2300-380 of such, as was conducted inthis work: relative step of ducts of S/dz, diameters of ducts of grids of dz on efficiency of work of heater highpressure turbine of K-500-240 in the areas of heating.
Keywords: подогрев конденсата; теплота отборов; аппараты теплообменные